2016
DOI: 10.1186/s11671-016-1516-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of TiO2 Nanotube Array Gas Sensor for SF6-Insulated Equipment Detection: a Review

Abstract: Since Zwilling and co-workers first introduced the electrochemical anodization method to prepare TiO2 nanotubes in 1999, it has attracted a lot of researches due to its outstanding gas response and selectivity, making it widely used in gas detection field. This review presents an introduction to the sensor applications of TiO2 nanotube arrays (TNTAs) in sulfur hexafluoride (SF6)-insulated equipment, which is used to evaluate and diagnose the insulation status of SF6-insulated equipment by detecting their typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The team also discussed TiO 2 nanotube arrays and the adsorption of SO 2 , SOF 2 , and SO 2 F 2 on different surface of TiO 2 . The gas sensing responses of Pt, Au-modified TiO 2 are better than pure TiO 2 (Zhang et al, 2016). Although the most of present studies focus on the TiO 2 and carbon nanotubes, the hollow structure and density functional theory calculations can inspire further research on the detection of SF 6 decomposing products.…”
Section: Gas Sensing Mechanismmentioning
confidence: 96%
“…The team also discussed TiO 2 nanotube arrays and the adsorption of SO 2 , SOF 2 , and SO 2 F 2 on different surface of TiO 2 . The gas sensing responses of Pt, Au-modified TiO 2 are better than pure TiO 2 (Zhang et al, 2016). Although the most of present studies focus on the TiO 2 and carbon nanotubes, the hollow structure and density functional theory calculations can inspire further research on the detection of SF 6 decomposing products.…”
Section: Gas Sensing Mechanismmentioning
confidence: 96%
“…For the past few years, it has become the new trend to develop the pint-sized gas-detecting device by using the gas-sensing technology, which is aimed at achieving on-line monitoring to dissolved gas in transformer oil and grasping the operational state of equipment at any time [11,12]. On-line monitoring of dissolved gas analysis could help reduce the unavailability of equipment in the long run-time [13], thus it can improve the economic benefit, optimize cycle and content of maintenance job to decrease maintenance fee and improve control of power system and the reliability of monitoring performance in overload operation [14].…”
Section: The Significance Of Dissolved Gases Detection In Oil-insulatmentioning
confidence: 99%
“…However, partial discharge and disruptive discharge might occur in GIS equipment during the long run, accounting for the SF 6 gas decomposing to various decomposition components, such as H 2 S, SO 2 , SOF 2 , SO 2 F 2 (Tsai, 2007; Liu et al, 2017). Previous researches have reported that these typical decomposition components are able to accelerate the corrosion rate of the GIS equipment and increase the paralysis possibility of the power system (Zhang X. et al, 2016; Li et al, 2017). Therefore, accurate and effective detection of SF 6 gas decomposition components is significant to estimate and optimize the operation state of GIS power equipment.…”
Section: Introductionmentioning
confidence: 99%